The Role of a Notary in Making a Deed of Power of Attorney to Charge a Mortgage on Land Collateral that Has Not Been Certified at Bank Jateng Purwodadi - Aziz Pujiharto, Abdul'; Fajar Riyanto, Taufan (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
The presence of notaries is increasingly important for Indonesian society today whose economy continues to develop. People use notary services to provide legal certainty in the field of obligations and agreements. SKMHT is an abbreviation of Power of Attorney to Charge Mortgage Rights. This power of attorney is given by the mortgagee to the creditor as the recipient of the mortgage right to charge the mortgage right on the object of the mortgage right. This SKMHT is a special power of attorney that gives special authority to the creditor to charge the mortgage right. This letter must be made with a notarial deed or PPAT deed. The purpose of this study is to determine and analyze the role of Notaries in making a Deed of Power of Attorney to Charge Mortgage Rights on uncertified land collateral at Bank Jateng Purwodadi Branch. To determine and analyze the obstacles faced by Notaries and solutions in making a Deed of Power of Attorney to Charge Mortgage Rights on uncertified land collateral at Bank Jateng Purwodadi Branch. This research employs an empirical legal approach, and its specifications employ a descriptive analytical method with a qualitative approach. The data sources and types used in this study are primary data obtained from field studies using interviews. Secondary data are obtained from literature studies related to the theory of legal certainty and authority. Based on the results of the research that the role of the Notary in making the deed of Power of Attorney to Charge Mortgage Rights (SKMHT) against uncertified land collateral at Bank Jateng Purwodadi Branch in practice the Notary makes the SKMHT in accordance with Article 15 UUHT to bind the guarantee for uncertified lands that will be used as collateral, and has fulfilled as stipulated in Article 38 UUJN regarding the beginning of the Deed, the body of the Deed, and the closing of the Deed. The obstacles faced by the Notary in making the SKMHT deed against uncertified land collateral at Bank Jateng Purwodadi Branch are a). Inhibiting factors from the Bank, namely incomplete documents, b). Inhibiting factors from the Debtor, namely the problem of the amount of fees. c). Bad Credit. The solutions to overcome these obstacles are: a). Giving 7 working days to complete the documents from the Bank or customer. b). Negotiating costs with the Notary, c). The Bank's caution in providing credit.